Pupuh Pangkur in Serat Wulangreh towards Javanese Youth Building Character: Lesson Learned from School-aged Children in Surakarta - Sulistyo, Edy Tri (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed at exploring the Javanese ethics and traditional teachings through understanding the Javanese texts. This was studied to find basic and comprehensive information about positive values establishing Javanese noble character manifested from and its implementation to the modern Javanese society and its relation to the concept of preserving arts and culture in accordance with Javanese philosophy. The study was designed with a qualitative paradigm conducted through explorative and survey methods. The data were collected through detailed interviews, observation, and documents/records analysis, as well as a literature review. The data were then analyzed using a contextual pragmatic analysis model. The study suggests that philosophical values implementation of pupuh pangkur to school-aged children is highly necessary, and the result is used as a recommendation for the development of school curriculum.